Symmetric anion exchange membranes enhance arsenic removal and overcome conductivity limitations in FCDI systems - Siyao Zhang; Purui Wang; Wenchao Xue; Wanni Zhang; Fangyuan Liu; Chaoge Yang; Hanlong Liu; Yang Zhang; Zimeng Zhang; Chunpeng Zhang (npj Clean Water)
Abstract Conventional flow-electrode capacitive deionization (FCDI) often exhibits performance constraints stemming from elevated ion migration resistance associated with diminished conductivity within the desalination chamber, particularly under complex aqueous matrices. This investigation introduces a symmetric anion-exchange membrane (AEM) configuration engineered to circumvent these conductivity limitations and enhance arsenic removal efficacy. Relative to conventional designs, the symmetric-AEM configuration demonstrated an approximate 19.4% enhancement in arsenic removal efficiency. For influent streams with initial arsenic concentrations of 1000 μg·L⁻¹, effluent concentrations were diminished below the analytical detection limit (0.02 μg·L⁻¹) employing a two-stage sequential process. This configuration sustains or potentially enhances desalination-chamber conductivity by optimizing ion migration pathways and facilitating anion compensation via highly mobile chloride ions. The contributions of chloride ions as supporting electrolytes and the transformations of arsenic valence states were interrogated, providing mechanistic insights into the observed performance improvements. Our findings signify a practical advancement in FCDI, presenting a potentially robust and efficacious strategy for arsenic remediation in contaminated groundwater. Thus, the symmetric-AEM configuration represents a significant advancement toward the broader implementation and practical application of FCDI systems for potable water production.